2003
DOI: 10.1161/01.atv.0000093546.10162.b2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Stretch Regulate Intercellular Communication in Vascular Smooth Muscle Cells Through Reactive Oxygen Species Formation

Abstract: Objective-We hypothesized that the alterations in vasomotor tone and adaptive remodeling responses that occur in the circulation because of hypoxia were dependent on changes in cell to cell communication through regulation of gap junction protein expression and function. Consequently, we studied the amount, distribution, and permeability of the principal vascular smooth muscle cell (VSMC) gap junction protein, connexin43, in rat aortic cultures exposed to oxygen partial pressures of 150 or 15 mm Hg. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
2
24
0
2
Order By: Relevance
“…In any case, the involvement of Cx43-based channels in the control of vasomotor tone is consistent with the finding that tensile stretch increased the expression of this connexin as well as gap junction intercellular communication in vascular smooth muscle cells (Cowan et al, 1998). Interestingly, this response was mediated by the formation of reactive oxygen species (Cowan et al, 1998;Cowan et al, 2003), which has been reported to contribute to the initiation of the myogenic constriction in mouse-tail arterioles (Nowicki et al, 2001). …”
Section: Gap Junctions In Vascular Smooth Musclesupporting
confidence: 86%
“…In any case, the involvement of Cx43-based channels in the control of vasomotor tone is consistent with the finding that tensile stretch increased the expression of this connexin as well as gap junction intercellular communication in vascular smooth muscle cells (Cowan et al, 1998). Interestingly, this response was mediated by the formation of reactive oxygen species (Cowan et al, 1998;Cowan et al, 2003), which has been reported to contribute to the initiation of the myogenic constriction in mouse-tail arterioles (Nowicki et al, 2001). …”
Section: Gap Junctions In Vascular Smooth Musclesupporting
confidence: 86%
“…In addition, the reduced ACh-induced relaxation in the pulmonary arteries of hypoxic and MCT-treated rats probably is not caused by decreased endothelial cholinergic receptors or NO synthase, because the pulmonary artery relaxation by the NO donor SNP was also reduced in PH rats. Although the reduced ACh relaxation in the PH rats could be due to increased oxidative stress and decreased NO bioavailability in hypoxic rats (Cowan et al, 2003), it cannot account for the reduced ACh relaxation in the MCT-treated rats. In addition, the enhanced PHE contraction in L-NAME-or ODQ-treated pulmonary arteries of hypoxic rats suggests that NO production/bioavailability was not significantly compromised.…”
Section: Discussionmentioning
confidence: 90%
“…This is unlikely the only mechanism, because blockers of NO-cGMP enhanced Phe contraction in pulmonary arteries of hypoxic and MCT rats with or without acidosis, suggesting possible compensatory activation of the NO-cGMP pathway in experimental PH. The reduced ACh relaxation in the PH rats and its improvement with acidosis is also unlikely due to decreased NO bioavailability due to increased oxidative stress in the setting of hypoxia (16), because ACh-induced relaxation was also reduced in the MCT model and improved during induction of acidosis in MCT rats. A plausible explanation for the reduced ACh relaxation in hypoxic and MCT-treated rats is possible structural changes in the pulmonary vascular wall and decreased responsiveness of pulmonary VSMCs to vasodilators.…”
Section: Discussionmentioning
confidence: 96%